2019
DOI: 10.1111/jebm.12188
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of evidence‐based guidelines in ventilator‐associated pneumonia prevention

Abstract: The level of knowledge regarding VAP prevention seems inadequate in the present study. Although having knowledge about the principles of evidence-based care cannot guarantee the implementation of these principles, lack of knowledge may be a potential barrier to adherence to evidence-based guidelines for the prevention of VAP. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 17 publications
1
27
0
2
Order By: Relevance
“…Generally, reasonable and stable P cuff can not only ensure enough supply of tidal volume but can also effectively prevent the aspiration of secretions into the lung, thereby reducing the incidence of VAP. Currently, the guidelines for VAP prevention (Torres et al, ; Klompas et al, ; Yeganeh et al, ) recommend maintaining the P cuff around 25 cmH 2 0 and monitoring and adjusting the P cuff thrice a day but make no recommendation on the use of continuous or intermittent endotracheal tube P cuff control system; however, it still warrants more studies to evaluate the role of continuous and intermittent control of P cuff . It is noteworthy that a patient's breathing, cough and medical operation characteristics, such as suction and body position, the drug use of sedations and muscle relaxants and the changes in body temperature, can also disturb the stability of P cuff (Vyas et al, ; Nseir et al, ; Nseir et al, ; Yang et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, reasonable and stable P cuff can not only ensure enough supply of tidal volume but can also effectively prevent the aspiration of secretions into the lung, thereby reducing the incidence of VAP. Currently, the guidelines for VAP prevention (Torres et al, ; Klompas et al, ; Yeganeh et al, ) recommend maintaining the P cuff around 25 cmH 2 0 and monitoring and adjusting the P cuff thrice a day but make no recommendation on the use of continuous or intermittent endotracheal tube P cuff control system; however, it still warrants more studies to evaluate the role of continuous and intermittent control of P cuff . It is noteworthy that a patient's breathing, cough and medical operation characteristics, such as suction and body position, the drug use of sedations and muscle relaxants and the changes in body temperature, can also disturb the stability of P cuff (Vyas et al, ; Nseir et al, ; Nseir et al, ; Yang et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to and knowledge about VAP prevention measures were shown to be poor in several studies 19 25 , 26 Adherence can be raised through different implementation programs 19 27 A systematic review identified education (eg, training sessions or development of concise summaries of the evidence) and execution strategies (eg, standardization of care processes and building redundancies into routine care) as strategies to enhance the adoption of VAP prevention measures 28 .…”
mentioning
confidence: 99%
“…Shin and Lee (2017) showed the social and organizational factors such as greater opportunities to exchange nurses' ideas and the communication skills as facilitators of EBP in nursing (12). Yeganeh et al (2016) resulted application of guidelines in nursing practice was a facilitator and lack of knowledge of nurses about it was a barrier in EBP (13). Black et al (2015) confirmed studies about knowledge, skills, facilitators, and barriers bridged the gap between practice and knowledge (14).…”
Section: Introductionmentioning
confidence: 89%